Outcome with early invasive versus conservative approach in patients over 75 years of age with non-ST-segment elevation myocardial infarction. (3rd May 2023) - Gjana, A; Pavli, E; Kristo, A; Zebi, A; Duka, A; Sharka, I; Seiti, J; Kresto, L; Xhafaj, M; Hasimi, E; Voci, A; Pane, E; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Non-ST elevation myocardial infarction (NSTEMI) is a common cause of hospitalization for patients aged 75 years or older. The current guidelines recommend an early invasive approach for patients with NSTEMI who are at moderate to high risk, but have no specific consideration for the elderly. Data from clinical trials for this group of patients are lacking. We present short term outcomes of patients aged 75 years or older diagnosed with NSTEMI treated with an early invasive strategy versus conservative strategy. Purpose: To evaluate short term outcome in NSTEMI patients >75 years of age who were treated with early invasive strategy versus conservative strategy. Methods: We reviewed data from 201 patients > 75 years of age who presented with NSTEMI from August 2021 to February 2022. 96 (47%) patients underwent early invasive treatment and 105 (53%) were treated conservatively. The decision for the conservative treatment was based on the decision of the attending cardiologist and the preference of the patient. Primary endpoint was mortality at 3-month follow-up. Secondary endpoints were recurrent myocardial infarction, re-intervention and length of hospital stay. Results: The mean age was 80.74 ± 3.7 years, ranging from 75 to 92 years old. Patients in the conservative group were more frequently affected from hypertension, heart failure, stroke and acute renal failure. Other basal characteristics were not statistically significant different between two groups. In-hospital mortality in the conservative group was higher than the invasive group (1.04% vs. 2.8%, p=0.037). 30-day survival was higher in the invasive group compared to the conservative group (94.8% vs. 82.4%, p=0.007) and 90-day survival was also higher in the invasive group compared to the conservative group (91.9% vs. 71%, p=0.001).There were no statistically significant differences with regard to secondary endpoints. In the multivariate analysis, ejection fraction <40% and hemoglobin level <10 mg/dL were inversely related to survival while an early invasive strategy was associated with improved survival at 3 months. Conclusion: Among NSTEMI patients older than 75 years, an early invasive treatment is associated with a lower in-hospital mortality and better 3-month survival.